Carcinoembryonic Antigen: A Potential Biomarker to Evaluate the Severity and Prognosis of COVID-19 - Chen, Qianqian; Kong, Hui; Qi, Xu; Ding, Wenqiu; Ji, Ningfei; Wu, Chaojie; Huang, Chaolin; Wu, Wenjuan; Huang, Mao; Xie, Weiping; Liu, Yun; Tang, Jinhai (Frontiers in Medicine, 2020)
Background and Objectives: Corona Virus Disease 2019 (COVID-19) has become a serious pandemic disease worldwide. Identification of biomarkers to predict severity and prognosis is urgently needed for early medical intervention due to high mortality of critical cases with COVID-19. This retrospective study aimed to indicate the values of carcinoembryonic antigen (CEA) in evaluating the severity and prognosis of COVID-19. Methods: We included 46 death cases from intensive care unit and 68 discharged cases from ordinary units with confirmed COVID-19 of Wuhan Jin Yin-tan Hospital from January 1 to March 22, 2020. Laboratory and radiologic data were analyzed retrospectively. All patients were followed up until April 10, 2020. Results: COVID-19 patients in the death group had significantly higher CEA levels (ng/ml) than discharged group (14.80 ± 14.20 vs. 3.80 ± 2.43, P < 0.001). The risk of COVID-19 death increased 1.317 times for each additional 1 ng/ml CEA level (OR = 1.317, 95% CI: 1.099–1.579). The standardized and weighted receiver operating characteristic curve (ROC) analysis adjusted to age, sex, and ferritin levels suggested that the area under the curve (AUC) of the serum CEA levels was 0.808 in discrimination between death cases and discharged cases with COVID-19 (P < 0.001). We found mortality of COVID-19 is associated with elevated CEA levels increased (HR = 1.023, 95% CI: 1.005–1.042), as well as age (HR = 1.050, 95% CI: 1.016–1.086) and ferritin levels (HR = 1.001, 95% CI: 1.001–1.002) by survival analysis of Cox regression model. Among discharged patients, CEA levels were significant lower in moderate cases compared to the severe and critical cases (P = 0.005; OR = 0.488, 95% CI: 0.294–0.808) from binary logistic regression analysis. The AUC of CEA levels was 0.79 in distinguishing moderate cases from discharged COVID-19 patients by standardized and weighted ROC analysis (P < 0.001). A positive correlation between CEA levels and CT scores existed in discharged patients (Correlation Coefficient: 0.687; P < 0.001). Conclusions: Elevated CEA levels increased the risk of death from COVID-19 and CEA levels were related to CT scores of the discharged patients positively.